Pimbek . no. 2, 1981 - NSZZ "Solidarność" w PIMB [Przemysłowym Instytucie Maszyn Budowlanych], [ed. Mirosław Eychler et al.] (NSZZ "Solidarność" PIMB, 1981)
Creation and circulation: For organizational use